2016
DOI: 10.1186/s12889-016-3306-4
|View full text |Cite|
|
Sign up to set email alerts
|

The concurrence of musculoskeletal pain and associated work-related factors: a cross sectional study

Abstract: BackgroundSeveral recent studies have described the presence of musculoskeletal complaints, presenting evidence that multisite musculoskeletal pain (MP) is more often present than single-site musculoskeletal pain. However, less is known about determinants of this multimorbidity, particularly, concerning the role of occupational factors and, mainly, what determines single or multisite pain. This study described the associations between pain in different body sites and investigated related factors to MP in worke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 32 publications
5
31
0
4
Order By: Relevance
“…First, undergraduates with current knee symptoms/injuries have an increased risk of having pain in other body regions (e.g., neck, shoulder, elbow, wrist/fingers, upper back, lower back, hip/thigh and ankle). This finding concurred with previous research that workers with knee pain often experienced other concurrent musculoskeletal pain (ranging from 27.1 to 45.0% depending on the body region) [32]. Similarly, high prevalence of co-existing knee and neck symptoms have been reported in a general adult population [33].…”
Section: Discussionsupporting
confidence: 91%
“…First, undergraduates with current knee symptoms/injuries have an increased risk of having pain in other body regions (e.g., neck, shoulder, elbow, wrist/fingers, upper back, lower back, hip/thigh and ankle). This finding concurred with previous research that workers with knee pain often experienced other concurrent musculoskeletal pain (ranging from 27.1 to 45.0% depending on the body region) [32]. Similarly, high prevalence of co-existing knee and neck symptoms have been reported in a general adult population [33].…”
Section: Discussionsupporting
confidence: 91%
“…After publication of the original article [1] it was brought to our attention that author Silvana Maria Santos Pataro was incorrectly included as Silvana Maria da Silva Pataro. The correct spelling of the name is included in the author list of this erratum.…”
Section: Erratummentioning
confidence: 99%
“…Other studies had samples between a few hundred18–21 27–31 33 up to about 1000 individuals22 24 32 on a diversity of occupations (eg, agricultural,20 30 extraction/manufacturing,24 27 31 33 factory workers,18 25 29 healthcare,19 34 education,26 craft workers,21 office workers28 or mixed22). In these studies, the highest MSP prevalence is reported for LBP (be that 7-day estimates: 17%25 and 18%26; or 12-month estimates: 18%,26 30%,25 44%22 and 57%33) and the upper extremities (19% for 7-day estimates23 and 32% for 12-month estimates24). …”
Section: Introductionmentioning
confidence: 98%